A Multicenter Study to Evaluate Subject Satisfaction With Two Treatments of AbobotulinumtoxinA a Year in the Glabellar Lines. Issue 4 (April 2021) - Schlessinger, Joel; Cohen, Joel L.; Shamban, Ava; Jacob, Carolyn; Karimi, Kian; Maas, Corey; Lane, Vanessa; Coquis-Knezek, Sarah; Meckfessel, Matthew
Abstract : BACKGROUND: Real-world re-treatment intervals for botulinum toxins vary, but most subjects receive treatment less frequently than the manufacturer-recommended minimum intervals. In subjects receiving treatment with AbobotulinumtoxinA (ABO) less frequently, high levels of satisfaction and psychosocial improvements in well-being, self-confidence, and quality of life are observed. OBJECTIVE: To evaluate subject satisfaction with a twice yearly re-treatment schedule. METHODS AND MATERIALS: This open-label, multicenter, interventional study evaluated subject satisfaction following injections of ABO 50 U in the glabellar lines at baseline and 6 months. The primary end point was subject satisfaction at 12 months. Secondary endpoints included subject satisfaction, FACE-Q scales, and glabellar line severity scale (GLSS). RESULTS: Ninety-five percent of the 120 subjects were "highly satisfied" or "satisfied" with their treatment outcomes at 12 months. FACE-Q total scores suggested that subjects were less bothered by glabellar lines and felt better about their facial appearance with each treatment versus baseline. Approximately half of subjects had ≥1-grade improvement from baseline in GLSS at 12 months. Median onset of effect was 2 days. CONCLUSION: The majority of subjects (95%) were satisfied with ABO treatment every 6 months; results were supported by high subject satisfaction, long duration, rapid onset, natural-looking results, and overall psychological wellness and safety. Abstract : Supplemental Digital Content is Available in the Text.